Characteristics of agricultural and occupational injuries by workers' compensation and other payer sources. Issue 11 (22nd August 2019) - Missikpode, Celestin; Peek‐Asa, Corinne; Wright, Brad; Ramirez, Marizen
Abstract: Background: Workers' compensation claims data are routinely used to identify and describe work‐related injury for public health surveillance and research, yet the proportion of work‐related injuries covered by workers' compensation, especially in the agricultural industry, is unknown. Methods: Using data from the Iowa Trauma Registry, we determined the sensitivity and specificity of the use of workers' compensation as a payer source to ascertain work‐related injuries requiring acute care comparing agriculture with other rural industries. Results: The sensitivity of workers' compensation as a payer source to identify work‐related agricultural injuries was 18.5%, suggesting that the large majority of occupational agricultural injuries would not be accurately identified through workers' compensation records. For rural nonagricultural, rural occupational injuries, the sensitivity was higher (64.2%). Work‐related agricultural injuries were most frequently covered by private insurance (39.6%) and public insurance (21.4%), while rural nonagricultural injuries were most frequently covered by workers' compensation (65.2%). Conclusions: Workers' compensation claims data will not include the majority of work‐related agricultural injuries.